The Role of the Adult with Disabilities’ Family in the Labor Inclusion Processes: A Challenge for Special Education in Costa Rica - Madrigal-Lizano, Ana Magaly (2015)
The following essay presents the author’s thoughts regarding positive and negative family impacts of the process of including the adult with disabilities. It also discusses the significance and challenges faced by those teachers and schools in charge of special education based on the responsibility of establishing the most mechanisms possible to provide, along with their families, a free environment when it comes to decision making for the population with disabilities in regards to their job future and the special skills needed to provide a free independent lifestyle.  The essay focuses on a social model in an inclusive paradigm based on a human rights perspective. In accordance with Vargas (2012), it suggests a social model that highlights social barriers and their environment with a holistic view, which does not exclude individual intervention but emphasizes the inclusion of this population in a world which has been designed by and for people that do not experience any disability.  When shifting from the medical model to the social one, responsibility is also transferred to the social and political aspects, hence making the family a relevant pillar to be considered in different training and information environments in support of the adult with disabilities who needs and deserves the opportunity of having a job as a way to be autonomous and independent.